Reshaping Governance: Mainstreaming Co-Production in the Megaproject Development of Nusantara Capital City, Indonesia - Mardianti, Elis; Ghofiqi, Muhammad Dzulfikar Al; Suaedi, Falih; Setijaningrum, Erna; Asmorowati, Sulikah (Universitas Teuku Umar, 2025)
Many large-scale development projects, including Indonesia’s new capital relocation, face challenges in ensuring inclusive and participatory governance. The development of Nusantara Capital City (IKN) has been marked by limited public consultation, rapid policy formulation, and marginalization of local communities, leading to recurring resistance at various levels. These issues threaten the achievement of SDG 11 (Sustainable Cities and Communities) and SDG 16 (Peace, Justice, and Strong Institutions), both of which emphasize inclusive and transparent governance. This study explores co-production as a governance approach to enhance citizen engagement in the context of IKN’s development. Employing a qualitative literature review, it examines how co-production is conceptualized and practiced in the planning of IKN. The findings indicate that while co-production is recognized in official discourse, its implementation remains limited and fragmented. Key barriers include weak legal frameworks, lack of institutional mechanisms, and absence of a formal oversight body. Strengthening co-production is crucial for ensuring transparency, inclusivity, and accountability in IKN’s governance. The study proposes a comprehensive framework involving legal reforms, institutionalization of participatory mechanisms, and enhanced accountability tools. These efforts are vital to transform IKN from a top-down megaproject into a model of inclusive urban governance.